ANALISIS DITERMINAN PERMINTAAN PEMBIAYAAN PEDAGANG MIKRO (STUDI KASUS PEDAGANG TRADISIONAL KOTA PADANGSIDIMPUAN - windari, windari windari (AL-QARDH, 2019)
The purpose of this study is to find out what are the determinants that influence the demand for financing micro traders, and which factors are the most dominant. The main sub-topic of this research is micro traders who are classified as UMKM, in the entire City of Padangsidimpuan, namely the pasar sagumpal bonang, pasar ucok kodok, pasar Impres Sadabuan pasar Saroha with 180 respondents. The technique used in this study is a qualitative analysis by describing or describing the actual state of the research object. The results of this study are the determinants that influence the demand for micro trader financing in the city of Padangsidimpuan, which are Capital Deficiency or business development, Easier / lighter administration, Banking Knowledge, and interest rates / profit sharing. Whereas the determining factor which is the most dominant in influencing the demand for financing is easier / lighter administration.